Transient convection finite difference solution - Agapin, Dennis Rio (2010)
Most commonly encountered studies of convection do not deal with time-variable conditions, but rather permanent conditions i.e. stationary velocity and temperature fields. This is probably due to calculation difficulties in terms of time and cost of computation. Transient conversion deals with time-variable boundary layer equations. In this study, we will investigate transient convection in a horizontal rectangular enclosure where one wall is at a high temperature, the other wall is at a low temperature and the other two walls are adiabatic.
After setting up the governing partial differential equations to be used, the finite difference method will be applied. This will involve using non-dimensional variables and discretization of such variables. Then the program Matlab 6 will be used to obtain the solution.
The results will show the behavior of temperature and stream function at each time increment, starting from time equal to zero up to the steady state time. As expected, since symmetry can be found in the boundary conditions, then symmetry was also present at every stage of the transient solution.
"October 2010"
Thesis (M.S. Mechanical Engineering)--University of the Philippines Diliman
Keywords: Heat -- Convection; Differential equations, Partial